PENGEMBALIAN KERUGIAN NEGARA MELALUI SOCIAL CORRUPTION COST SEBAGAI SARANA PEBERANTASAN TINDAK PIDANA KORUPSI PADA MASA TRANSISI TEKNOLOGI - Faisol (LP3M, 2024)
Recovering state losses through Social Corruption Cost is the main focus of efforts to eradicate corruption in the era of technological transition. The development of information technology has changed the landscape of corruption, with increasingly digitized and complex corruption practices. This paper discusses the concept of Social Corruption Cost as a tool to measure social losses caused by corruption, including its impact on the economy, public services, and public trust in government. It also explores the legal and policy measures that can be taken to recover state losses caused by corruption, focusing on the application of Social Corruption Cost as a recovery method. Through analysis of current literature and data, this research aims to provide a better understanding of the role of Social Corruption Cost in fighting corruption amidst technological change. It is hoped that this research can provide valuable insights for policymakers, legal practitioners, and academics in their efforts to improve the effectiveness of fighting corruption in times of technological transition.